Method for preparing microporous copper foil material and product thereof
Through roller screen printing and UV light irradiation curing combined with electrolysis, the preparation process of microporous copper foil materials is simplified, the problems of complex processes and high costs in the existing technology are solved, the performance controllability and mechanical properties are improved, and the special application needs are met. .
Patent Information
- Application Number
- CN202411369799.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2024-12-27
AI Technical Summary
The existing preparation methods for microporous copper foil materials have problems such as complex preparation process, high cost, difficult performance to control, and low tensile strength and elongation, which cannot meet the needs of some special applications.
Using roller screen printing technology and UV light irradiation curing, combined with electrolysis, microporous copper foil materials are prepared. By accurately controlling the number of screen printing mesh, ink coating and UV light irradiation parameters, the preparation process is simplified, the cost is reduced, and the micropore size is increased. and distribution uniformity, improving tensile strength and elongation.
It has achieved simplification of the preparation process, reduced costs, improved performance controllability, improved tensile strength and elongation of microporous copper foil materials, met more special application needs, and improved conductivity.
Smart Images

Figure CN119194540A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of microporous copper foil, in particular to a method for preparing a microporous copper foil material and a product thereof. Background Art
[0002] Copper foil is a metal material with good electrical and thermal conductivity, and is widely used in electronics, electrical, machinery and other fields. With the development of science and technology, microporous copper foil materials have been widely used in battery manufacturing, filtration technology, electromagnetic shielding and other fields due to their unique properties, such as high specific surface area, good air permeability and heat dissipation. The preparation methods of microporous copper foil materials mainly include electroforming, chemical etching, laser drilling and the like. 2) Solutions of the prior art: Existing microporous copper foil materials are mainly prepared by electroforming. The electroforming method is to form copper foil by depositing copper ions in the electrolyte on the cathode surface, and then forming micropores on the copper foil by physical or chemical methods. In addition, there is also a method of forming micropores on copper foil by chemical etching. However, these methods often require complex process flows and expensive equipment, and the performance of the prepared microporous copper foil materials is not easy to control. 3) Problems of the existing technology: The existing methods for preparing microporous copper foil materials have the following main problems: First, the preparation process is complicated and the cost is high; second, the performance of the prepared microporous copper foil material is difficult to control, such as the pore size and distribution uniformity; third, the tensile strength and elongation of the existing microporous copper foil material are low, which cannot meet the needs of some special applications. Therefore, how to prepare high-performance microporous copper foil materials simply and at low cost is an urgent problem to be solved in the current copper foil preparation technology field.
[0003] The prior art method for preparing microporous copper foil still has the following problems:
[0004] 1) The preparation process of microporous copper foil material is complicated and the cost is high;
[0005] 2) The properties of the prepared microporous copper foil material are difficult to control, such as pore size and distribution uniformity;
[0006] 3) The tensile strength and elongation of existing microporous copper foil materials are low and cannot meet the needs of some special applications;
[0007] In view of the above problems, a method for preparing a microporous copper foil material and a product thereof are provided. Summary of the invention
[0008] The purpose of the present invention is to provide a method for preparing a microporous copper foil material and a product thereof, so as to solve the problems raised in the above background technology. To achieve the above purpose, the present invention provides the following technical solution: a method for preparing a microporous copper foil material and a product thereof, comprising the following steps:
[0009] Step 1, preparing a production equipment suitable for preparing microporous copper foil material;
[0010] Step 2: coating a layer of insulating tape with a width of 5 cm on the edge of the cathode surface of the production equipment;
[0011] Step 3, using roller screen printing technology, applying the diluted insulating ink material to the cathode surface coated with the insulating tape;
[0012] Step 4: After coating is completed, tear off the insulating tape on the edge;
[0013] Step 5, irradiating the cathode surface coated with the insulating ink material with UV light to solidify the ink;
[0014] Step six, placing the cured cathode in solution I and applying power for electrolysis to prepare a microporous copper foil.
[0015] Preferably, the cathode surface area of the production equipment in step 1 is 8-9 square meters.
[0016] Preferably, the insulating ink material is an environmentally friendly material, including but not limited to polyurethane acrylate.
[0017] Preferably, the dilution ratio of the polyurethane acrylate is 1:5.
[0018] Preferably, the UV light source is a high-pressure mercury lamp.
[0019] Preferably, the power of the high-pressure mercury lamp is 1000W, and the irradiation time is 15-20 minutes.
[0020] Preferably, the UV light intensity of the high pressure mercury lamp is about 80-100W.
[0021] Preferably, the solution I comprises 200 g / L copper sulfate, 50 g / L sulfuric acid, 50 mg / L chloride ions, and 5 ml / L additives.
[0022] Preferably, the temperature of the solution I is 25° C. and the pH value is 2.0.
[0023] Preferably, the current density during electrolysis in step six is 15A / dm2 and the electrolysis time is 30 minutes.
[0024] Compared with the prior art, the present invention has the following beneficial effects:
[0025] 1. Simplify the preparation process: The present invention adopts roller screen printing technology and UV light irradiation curing, as well as electrolysis to prepare microporous copper foil materials. Compared with traditional electroforming and chemical etching methods, the preparation process is simpler and the preparation cost is greatly reduced. 2. Improve performance controllability: The present invention can accurately control the size and distribution uniformity of micropores on the microporous copper foil material by accurately controlling the parameters of the screen printing yarn mesh number, ink coating and UV light irradiation curing in the roller screen printing technology, thereby improving the performance controllability of the product. 3. Excellent mechanical properties: The tensile strength of the microporous copper foil material prepared by the present invention is about 300-340MPa, and the elongation is about 1.5-2.5%. Compared with the existing microporous copper foil materials, it has better mechanical properties and can meet the needs of more special applications. 4. High conductivity: The resistivity of the microporous copper foil material of the present invention is 1.67μΩ·cm, which has better conductivity than non-porous copper foil. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 A flowchart of a method for preparing a microporous copper foil material and a product thereof according to the present invention;
[0027] Figure 2 A method for preparing a microporous copper foil material and XRD diagrams of the microporous copper foil and non-porous copper foil of the product of the present invention;
[0028] Figure 3 The present invention discloses a method for preparing microporous copper foil material and a screen and microporous copper foil diagram of the product. DETAILED DESCRIPTION
[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technical personnel in this field without creative work are within the scope of protection of the present invention.
[0030] Example 1
[0031] See also Figure 1 The present invention provides a technical solution: a method for preparing a microporous copper foil material and a product thereof, comprising the following steps:
[0032] Step 1, preparing a production equipment suitable for preparing microporous copper foil material;
[0033] Step 2: Apply a layer of insulating tape with a width of 5 cm on the edge of the cathode surface of the production equipment. Insulating tape, also known as insulating tape or tape tape, is a special adhesive tape commonly used by electricians in electrical operations. Its main function is to prevent leakage and provide insulation protection. With the development of science and technology and economy, many types of insulating tapes have appeared, but the most common ones are polyvinyl chloride and polyolefin insulating tapes. The insulating tape consists of a base tape and a pressure-sensitive adhesive layer. The insulating tape has excellent insulating properties, can effectively prevent damage to the equipment caused by current, is flame retardant, and can prevent the occurrence of fire to a certain extent; at the same time, it has good weather resistance, can maintain stable performance in a variety of environments, and has certain moisture-proof and mildew-proof properties. It is suitable for humid environments and can be used in occasions that require wear resistance and pressure resistance, such as the protection and fixation of wires in vehicles such as cars, trains, and ships. Insulating tapes are widely used in the fields of electricity, electrical, communications, and electronics. They are used for the insulation protection of various wires, cables, switches, sockets, and other equipment. In the power system, they prevent damage to the equipment caused by current and improve the safety of the equipment. In the home, they are used for the fixation and insulation protection of wires in household appliances such as televisions, refrigerators, and washing machines to avoid problems such as short circuits and leakage of wires. They are used for the binding and fixation of various wires to improve the stability and safety of the equipment. In some occasions where fire protection is required, such as the protection and fixation of wires for fire-proof equipment such as fire doors and fire windows in buildings;
[0034] Step three, using roller screen printing technology, apply the diluted insulating ink material to the cathode surface that has been coated with insulating tape. As a printing technology, roller screen printing mainly uses a roller as a printing carrier, and transfers ink or pigment to the substrate through a screen to achieve printing of patterns, text, etc. Roller screen printing is an efficient printing method, especially suitable for large-scale, high-precision printing needs. It is done by evenly applying ink or pigment on the roller, and then using the rotation of the roller to print the pattern or text on the substrate. Roller screen printing has the advantages of fast printing speed, high printing quality, and strong adaptability. It is widely used in packaging, advertising, decoration, electronics, toys and other fields. Select suitable rollers, screens, inks and substrates, and make screens according to the design pattern. The quality of the screen directly affects the printing effect. Apply the ink evenly on the roller to ensure the amount and uniformity of the ink. Place the substrate on the printing table, and the roller rotates and contacts the substrate to print the pattern or text on the substrate. After printing, the substrate needs to be dried to ensure the adhesion of the ink and the printing effect.
[0035] Step 4: After coating is completed, tear off the insulating tape on the edge;
[0036] Step 5, irradiating the cathode surface coated with the insulating ink material with UV light to solidify the ink;
[0037] Step six, placing the cured cathode in solution I and applying power for electrolysis to prepare a microporous copper foil.
[0038] In this embodiment, the cathode surface area of the production equipment in step 1 is 9 square meters.
[0039] In this embodiment, the insulating ink material is an environmentally friendly material, including but not limited to polyurethane acrylate. Polyurethane acrylate is a special chemical composite material, usually prepared by copolymerization of a mixture of polyurethane and acrylate compounds. The molecular structure of polyurethane acrylate contains both acrylic functional groups and urethane bonds, which makes it have the excellent properties of both materials. The polyurethane part is usually derived from the reaction of isocyanate and polyol, while the acrylate part includes acrylate monomers. The cured polyurethane acrylate adhesive has the high wear resistance, adhesion, flexibility, high peel strength and excellent low temperature resistance of polyurethane, and has the excellent optical properties and weather resistance of polyacrylate. Due to the presence of urethane bonds in the polyurethane film, a variety of hydrogen bonds can be formed between its molecular chains, which makes the material have excellent mechanical wear resistance and flexibility, high elongation at break, and the polyurethane acrylate resin also has high elasticity, bending and flexibility. The material has good resistance to dilute acid, dilute alkali, water, and organic solvents. The heat deformation temperature of polyurethane acrylate is usually between 60°C, and the coating has good adhesion to difficult-to-bond substrates, such as plastics. The composition and chemical properties of PUA have greater room for adjustment than epoxy resins, and a variety of PUA prepolymers with different functionalities and different properties can be synthesized, such as high hardness, high flexibility or high elasticity PUA cured films can be obtained. As a very important class of oligomers in the field of waterproof coatings, PUA is often used as an auxiliary functional resin to increase the flexibility of the coating, reduce stress shrinkage, and improve adhesion. In the field of composite materials, PUA can be used for the bonding between composite materials and metal frames, as well as the bonding of glass fiber reinforced plastics to metals. It can also be used in aerospace, electronics and electrical, metal materials, packaging materials, shipbuilding, textiles, rubber, ceramics, construction, automobiles and other industries.
[0040] In this embodiment, the dilution ratio of polyurethane acrylate is 1:5.
[0041] In this embodiment, the UV light source is a high-pressure mercury lamp. The high-pressure mercury lamp is a high-pressure mercury vapor discharge lamp with fluorescent powder coated on the inner surface of the glass shell. It has soft white light and simple structure, low cost, low maintenance cost, high light efficiency, long life, and energy saving. It is suitable for industrial lighting, warehouse lighting, street lighting, floodlighting, safety lighting and other fields. The high-pressure mercury lamp consists of a fluorescent bulb shell and a discharge tube. The discharge tube is thin and short, filled with high-pressure mercury vapor, and wrapped with a cotton ball-shaped fluorescent bulb shell. After power is turned on, the mercury vapor in the discharge tube is ionized and excited to form a discharge, and the collision between electrons, atoms and ions emits light. At the same time, the ultraviolet rays generated by the discharge tube irradiate the fluorescent bulb shell, further emitting a large amount of visible light. The visible spectrum lines mainly radiated by the high-pressure mercury lamp include 404.7 nm, 435.8nm, 546.1nm and 579.0nm. In addition, it also radiates strong long-wave ultraviolet rays of 365.0nm, which is generally around 4100K, but different types of high-pressure mercury lamps may have different color temperatures. The color rendering index of ordinary high-pressure mercury lamps is generally between 45, and the improved products may be higher. The color rendering index of ordinary high-pressure mercury lamps is generally between 45, and the improved products may be higher. The color rendering index of ordinary high-pressure mercury lamps is generally between 45, and the improved products may be higher. The color rendering index of ordinary high-pressure mercury lamps is generally between 45, and the improved products may be higher. It is not advisable to restart the lamp body before it is completely cooled down to avoid damage to the lamp. Mercury vapor leakage and lamp tube scrapping need to be properly handled to prevent soil and water pollution.
[0042] In this embodiment, the power of the high pressure mercury lamp is 1000W, and the irradiation time is 20 minutes.
[0043] In this embodiment, the UV light intensity of the high pressure mercury lamp is about 100W.
[0044] In this embodiment, solution I includes 200 g / L copper sulfate, 50 g / L sulfuric acid, 50 mg / L chloride ions, and 5 ml / L additives.
[0045] In this embodiment, the temperature of solution I is 25° C. and the pH value is 2.0.
[0046] In this embodiment, the current density during electrolysis in step six is 15A / dm2, and the electrolysis time is 30 minutes.
[0047] Example 2
[0048] See also Figure 1 The present invention provides a technical solution: a method for preparing a microporous copper foil material and a product thereof, comprising the following steps:
[0049] Step 1, preparing a production equipment suitable for preparing microporous copper foil material;
[0050] Step 2: Apply a layer of insulating tape with a width of 5 cm on the edge of the cathode surface of the production equipment. Insulating tape, also known as insulating tape or tape tape, is a special adhesive tape commonly used by electricians in electrical operations. Its main function is to prevent leakage and provide insulation protection. With the development of science and technology and economy, many types of insulating tapes have appeared, but the most common ones are polyvinyl chloride and polyolefin insulating tapes. The insulating tape consists of a base tape and a pressure-sensitive adhesive layer. The insulating tape has excellent insulating properties, can effectively prevent damage to the equipment caused by current, is flame retardant, and can prevent the occurrence of fire to a certain extent; at the same time, it has good weather resistance, can maintain stable performance in a variety of environments, and has certain moisture-proof and mildew-proof properties. It is suitable for humid environments and can be used in occasions that require wear resistance and pressure resistance, such as the protection and fixation of wires in vehicles such as cars, trains, and ships. Insulating tapes are widely used in the fields of electricity, electrical, communications, and electronics. They are used for the insulation protection of various wires, cables, switches, sockets, and other equipment. In the power system, they prevent damage to the equipment caused by current and improve the safety of the equipment. In the home, they are used for the fixation and insulation protection of wires in household appliances such as televisions, refrigerators, and washing machines to avoid problems such as short circuits and leakage of wires. They are used for the binding and fixation of various wires to improve the stability and safety of the equipment. In some occasions where fire protection is required, such as the protection and fixation of wires for fire-proof equipment such as fire doors and fire windows in buildings;
[0051] Step three, using roller screen printing technology, apply the diluted insulating ink material to the cathode surface that has been coated with insulating tape. As a printing technology, roller screen printing mainly uses a roller as a printing carrier, and transfers ink or pigment to the substrate through a screen to achieve printing of patterns, text, etc. Roller screen printing is an efficient printing method, especially suitable for large-scale, high-precision printing needs. It is done by evenly applying ink or pigment on the roller, and then using the rotation of the roller to print the pattern or text on the substrate. Roller screen printing has the advantages of fast printing speed, high printing quality, and strong adaptability. It is widely used in packaging, advertising, decoration, electronics, toys and other fields. Select suitable rollers, screens, inks and substrates, and make screens according to the design pattern. The quality of the screen directly affects the printing effect. Apply the ink evenly on the roller to ensure the amount and uniformity of the ink. Place the substrate on the printing table, and the roller rotates and contacts the substrate to print the pattern or text on the substrate. After printing, the substrate needs to be dried to ensure the adhesion of the ink and the printing effect.
[0052] Step 4: After coating is completed, tear off the insulating tape on the edge;
[0053] Step 5, irradiating the cathode surface coated with the insulating ink material with UV light to solidify the ink;
[0054] Step six, placing the cured cathode in solution I and applying power for electrolysis to prepare a microporous copper foil.
[0055] In this embodiment, the cathode surface area of the production equipment in step 1 is 8 square meters.
[0056] In this embodiment, the insulating ink material is an environmentally friendly material, including but not limited to polyurethane acrylate. Polyurethane acrylate is a special chemical composite material, usually prepared by copolymerization of a mixture of polyurethane and acrylate compounds. The molecular structure of polyurethane acrylate contains both acrylic functional groups and urethane bonds, which makes it have the excellent properties of both materials. The polyurethane part is usually derived from the reaction of isocyanate and polyol, while the acrylate part includes acrylate monomers. The cured polyurethane acrylate adhesive has the high wear resistance, adhesion, flexibility, high peel strength and excellent low temperature resistance of polyurethane, and has the excellent optical properties and weather resistance of polyacrylate. Due to the presence of urethane bonds in the polyurethane film, a variety of hydrogen bonds can be formed between its molecular chains, which makes the material have excellent mechanical wear resistance and flexibility, high elongation at break, and the polyurethane acrylate resin also has high elasticity, bendability and circumventability. The material has good resistance to dilute acid, dilute alkali, water, and organic solvents. The heat deformation temperature of polyurethane acrylate is usually between 50 and 60°C. The coating has good adhesion to substrates that are difficult to bond, such as plastics. The composition and chemical properties of PUA have greater room for adjustment than epoxy resins. A variety of PUA prepolymers with different functionalities and different properties can be synthesized, such as PUA cured films with high hardness, high flexibility or high elasticity. As a very important class of oligomers in the field of waterproof coatings, PUA is often used as an auxiliary functional resin to increase the flexibility of the coating, reduce stress shrinkage, and improve adhesion. In the field of composite materials, PUA can be used for bonding between composite materials and metal frames, as well as bonding between glass fiber reinforced plastics and metals. It can also be used in aerospace, electronics and electrical, metal materials, packaging materials, shipbuilding, textiles, rubber, ceramics, construction, automobiles and other industries.
[0057] In this embodiment, the dilution ratio of polyurethane acrylate is 1:5.
[0058] In this embodiment, the UV light source is a high-pressure mercury lamp. The high-pressure mercury lamp is a high-pressure mercury vapor discharge lamp with fluorescent powder coated on the inner surface of the glass shell. It has soft white light and simple structure, low cost, low maintenance cost, high light efficiency, long life, and energy saving. It is suitable for industrial lighting, warehouse lighting, street lighting, floodlighting, safety lighting and other fields. The high-pressure mercury lamp consists of a fluorescent bulb shell and a discharge tube. The discharge tube is thin and short, filled with high-pressure mercury vapor, and wrapped with a cotton ball-shaped fluorescent bulb shell. After power is turned on, the mercury vapor in the discharge tube is ionized and excited to form a discharge, and the collision between electrons, atoms and ions emits light. At the same time, the ultraviolet rays generated by the discharge tube irradiate the fluorescent bulb shell, further emitting a large amount of visible light. The visible spectrum lines mainly radiated by the high-pressure mercury lamp include 404.7 nm, 435.8nm, 546.1nm and 577.0nm. In addition, it also radiates strong long-wave ultraviolet rays of 365.0nm, which is generally around 4100K, but different types of high-pressure mercury lamps may have different color temperatures. The color rendering index of ordinary high-pressure mercury lamps is generally between 40, and the improved products may be higher. The color rendering index of ordinary high-pressure mercury lamps is generally between 40, and the improved products may be higher. The color rendering index of ordinary high-pressure mercury lamps is generally between 40, and the improved products may be higher. The color rendering index of ordinary high-pressure mercury lamps is generally between 40, and the improved products may be higher. It is not advisable to restart the lamp body before it is completely cooled down to avoid damage to the lamp. Mercury vapor leakage and lamp tube scrapping need to be properly handled to prevent soil and water pollution.
[0059] In this embodiment, the power of the high pressure mercury lamp is 1000W, and the irradiation time is 15 minutes.
[0060] In this embodiment, the UV light intensity of the high pressure mercury lamp is about 80W.
[0061] In this embodiment, solution I includes 200 g / L copper sulfate, 50 g / L sulfuric acid, 50 mg / L chloride ions, and 5 ml / L additives.
[0062] In this embodiment, the temperature of solution I is 25° C. and the pH value is 2.0.
[0063] In this embodiment, the current density during electrolysis in step six is 15A / dm2, and the electrolysis time is 30 minutes.
[0064] The above shows and describes the basic principles, main features and advantages of the present invention. Technical personnel in this industry should understand that the present invention is not limited to the above embodiments. The above embodiments and descriptions are only preferred examples of the present invention and are not used to limit the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. A method for preparing a microporous copper foil material and a product thereof, characterized in that: The steps include: Step 1, preparing a production equipment suitable for preparing microporous copper foil material; Step 2: coating a layer of insulating tape with a width of 5 cm on the edge of the cathode surface of the production equipment; Step 3, using roller screen printing technology, applying the diluted insulating ink material to the cathode surface coated with the insulating tape; Step 4: After coating is completed, tear off the insulating tape on the edge; Step 5, irradiating the cathode surface coated with the insulating ink material with UV light to solidify the ink; Step six, placing the cured cathode in solution I and applying power for electrolysis to prepare a microporous copper foil.
2. The method for preparing a microporous copper foil material and the product thereof according to claim 1, characterized in that: The cathode surface area of the production equipment in step 1 is 8-9 square meters.
3. The method for preparing a microporous copper foil material and the product thereof according to claim 1, characterized in that: The insulating ink material is an environmentally friendly material, including but not limited to polyurethane acrylate.
4. The method for preparing a microporous copper foil material and the product thereof according to claim 3, characterized in that: The dilution ratio of the polyurethane acrylate is 1:
5.
5. The method for preparing a microporous copper foil material and the product thereof according to claim 1, characterized in that: The UV light source is a high pressure mercury lamp.
6. The method for preparing a microporous copper foil material and the product thereof according to claim 5, characterized in that: The power of the high-pressure mercury lamp is 1000W, and the irradiation time is 15-20 minutes.
7. The method for preparing a microporous copper foil material and the product thereof according to claim 5, characterized in that: The UV light intensity of the high pressure mercury lamp is about 80-100W.
8. The method for preparing a microporous copper foil material and the product thereof according to claim 1, characterized in that: The solution I comprises 200 g / L of copper sulfate, 50 g / L of sulfuric acid, 50 mg / L of chloride ions, and 5 ml / L of additives.
9. The method for preparing a microporous copper foil material and the product thereof according to claim 1, characterized in that: The temperature of the solution I is 25° C., and the pH value is 2.
0.
10. The method for preparing a microporous copper foil material and the product thereof according to claim 1, characterized in that: The current density during electrolysis in step six is 15A / dm2, and the electrolysis time is 30 minutes.
